A Study Showing Relationship Between Knowledge And Awareness Regarding Learning Disability Among School Teachers (Journal of Namibian Studies : History Politics Culture, 2023)
There are distinct obstacles in the educational system for students with learning impairments, which are neurodevelopmental diseases affecting different cognitive functions. In order to meet the requirements of their students, educators must go beyond the scope of traditional curricula. In order to provide focused interventions and support, educators must first recognize that a student has a learning disability. The researchers used a self-administered questionnaire to conduct a cross-sectional study with 65 educators. A strong correlation was found between the knowledge level and the instructors' qualifications (P value < 0.001) and experience (P value < 0.05). The results highlight the critical need of educating educators about children's learning difficulties.